Sigma phase embrittlement-induced failures of heat-resistant stainless steel traveling grate links. (February 2023) - Kishore, Kaushal; Kushwaha, Sanjay; Sai Pranay Teja, Kayyam; Kumar Chandan, Avanish; Mukherjee, Monideepa; Adhikary, Manashi; Kumar, Anup
Highlights: Repeated failures of the traveling grate (TG) link of an iron Pellet Plant are investigated in detail. Analysis revealed a combination of intergranular crack initiation along pre-existing grain boundary chromium carbides followed by a transgranular brittle fracture due to sigma-phase induced embrittlement. In-service precipitation of deleterious sigma phase was confirmed using optical and scanning electron microscopy with EDS mapping coupled with X-ray diffraction analysis. Thermodynamic simulation suggested an inherently high propensity of used alloy composition for sigma phase precipitation in the service temperature. Modified alloy composition for reduced susceptibility to sigma phase embrittlement is recommended based on thermodynamics and kinetics simulation using JMatPro software. Abstract: Traveling grates (TG) are used as beds over which green pellets are subjected to a series of thermal cycles, namely preheating, induration, and firing to make the pellets suitable for charging in the blast furnaces of an integrated steel plant. In this work, chronic failures of TG links after a service life of 2.5–3 years are investigated. A comparative analysis of failed, used and new TG links was carried out. Fractography of the failed link revealed an intergranular brittle fracture near the surface followed by a transgranular fracture with a signature of decohesion in the bulk of the fracture surface. Microstructural analysis revealed the presence of pre-existing grain boundary chromium carbides (Cr23 C6 ) in the new (unused) link, which can facilitate easy crack initiation and propagation. Furthermore, failed and used TG link revealed the presence of extensive precipitation of needle-like sigma phase confirmed by a combination of X-ray diffraction and scanning electron microscopy coupled with energy dispersive spectroscopy techniques. Such precipitation of the sigma phase occurs during exposure to a susceptible high-temperature range. The presence of the sigma phase is known to embrittle the austenitic stainless steel and such embrittlement is confirmed by a significant increase in hardness and decrease in Charpy impact toughness of failed and used TG links compared to the new TG link. Thermodynamic and kinetic simulations confirmed a high susceptibility of the existing alloy composition to extensive sigma phase precipitation in a wide temperature range. A new alloy composition with higher nickel (∼30 wt%) and free from tungsten is proposed to reduce the susceptibility towards in-service embrittlement induced by sigma phase precipitation.